Crystallization and preliminary crystallographic studies of the hypothetical protein BPSL1038 from Burkholderia pseudomallei - Shaibullah, Sofiyah; Mohd-Sharif, Nurhikmah; Ho, Kok Lian; Raih, Mohd Firdaus; Nathan, Sheila; Rahmah, Mohamed; Ng, Chyan Leong (International Union of Crystallography, 2014)
Melioidosis is an infectious disease caused by the pathogenic bacterium Burkholderia pseudomallei. Whole-genome sequencing revealed that the B. pseudomallei genome includes 5855 coding DNA sequences (CDSs), of which 25% encode hypothetical proteins. A pathogen-associated hypothetical protein, BPSL1038, was overexpressed in Escherichia coli, purified and crystallized using vapour-diffusion methods. A BPSL1038 protein crystal that grew using sodium formate as precipitant diffracted to 1.55 A ° resolution. It belonged to space group C2221, with unit-cell parameters a = 85.36, b = 115.63, c = 46.73 A ° . The calculated Matthews coefficient (VM) suggests that there are two molecules per asymmetric unit, with a solvent content of 48.8%.